Counteranion driven homochiral assembly of a cationic C-3-symmetric gelator through ion-pair assisted hydrogen bond - Maity, Arunava; Gangopadhyay, Monalisa; Basu, Arghya; Aute, Sunil; Babu, Sukumaran Santhosh; Das, Amitava (Journal of the American Chemical Society, 2016)
The helical handedness in achiral self-assemblies is mostly complex due to spontaneous symmetry breaking or kinetically controlled random assembly formation. Here an attempt has been made to address this issue through chiral anion exchange. A new class of cationic achiral C-3-symmetric gelator devoid of any conventional gelation assisting functional units is found to form both right-and left-handed helical structures. A chiral counteranion exchange-assisted approach is successfully introduced to control the chirality sign and thereby to obtain preferred homochiral assemblies. Formation of anion-assisted chiral assembly was confirmed by circular dichroism (CD) spectroscopy, microscopic images, and crystal structure. The X-ray crystal structure reveals the construction of helical assemblies with opposite handedness for (+)- and (-)-chiral anion reformed gelators. The appropriate counteranion driven ion-pair-assisted hydrogen-bonding interactions are found responsible for the helical bias control in this C-3-symmetric gelator.

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2017)
Light harvesting donor-acceptor assemblies are indispensable to efficiently tap photons. In an attempt to improve the light harvesting efficiency of an acceptor doped assembly, we design and synthesize a donor-acceptor-donor triad which exhibits an exceptional intramolecular energy transfer with excellent efficiency. Moreover, a facile cascade energy transfer (energy funnelling) is observed in the presence of a series of second acceptors (63-91% efficiency) with tunable emission colours. Self-assembled nanosheets formed by the triad in the presence of acceptors exhibit cascade energy transfer assisted tunable emission. In addition, use of chiral acceptors induces chirality to the triad and results in the formation of chiral nanosheets alongwith cascade energy transfer. Here chiral induction, nanosheet formation and cascade energy transfer in the presence of chiral acceptors are used as tools to probe the intercalation of acceptor molecules in the donor scaffold.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule - Shivakumar, K.I.; Goudappagouda.; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2018)
We report a novel set of easily tailorable C-3 symmetric molecules with a pi-extended core and adorned with different thioalkyl groups, exhibiting solvatofluorochromic and amphoteric redox behaviour. The nearly planar core exhibits intermolecular face-to-face pi-stacking, S...S and intramolecular S...O interactions. Current-sensing atomic force microscopy studies revealed a high conductivity of similar to 0.15 mS cm(-1) in the undoped J-aggregate nanofibres of the thiopropyl appended gelator.

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping (vol 53, pg 7072, 2017) - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Correction for `Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping' by Goudappagouda et al., Chem. Commun., 2017, 53, 7072-7075.

Charge transfer liquid: a stable donor-acceptor interaction in the solvent-free liquid state - Wakchaure, Vivek Chandrakant; Pillai, Lekshmi, V; Goudappagouda; Ranjeesh, Kayaramkodath Chandran; Chakrabarty, Suman; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Charge-transfer complexes have been an inspiration to develop many functional soft materials. However, most of those studies have focused on solution based assemblies wherein the explicit control of solvents and their polarity are crucial. In this context, we explore an efficient and stable charge transfer liquid using a solvent-free liquid dialkoxynaphthalene donor and a naphthalenediimide acceptor. It has been observed that irrespective of the donor-acceptor ratio, the charge-transfer liquid exhibited an unprecedented stability and retained characteristic features even at increased temperatures. The underlying intermolecular interactions leading to efficient CT have been examined by NMR techniques together with theoretical modelling studies. The concept of charge transfer liquid will be highly beneficial for the development of processable optoelectronically active materials.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule (vol 54, pg 212, 2018) - Shivakumar, Kilingaru I.; Goudappagouda; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2019)
Correction for `Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule' by Kilingaru I. Shivakumar et al., Chem. Commun., 2018, 54, 212-215.

(Chiro)optical Properties of π-Extended Spiro-Double Carbo[7]helicene - Kumar, Viksit; Dongre, Sangram D.; Vandhanam, Aparna; Jadhav, Ashok Badrinarayan; Kumar, Jatish; Babu, Sukumaran Santhosh (Journal of Physical Chemistry Letters, 2025)
Helical nanographenes are a fascinating class of pi-extended chiral nanocarbons, where structural helicity imparts intrinsic chirality and unique optoelectronic properties to the rigid carbon framework. In this work, we synthesized a hexa-peri-hexabenzocoronene-based pi-extended spiro-double carbo[7]helicene. The helical distortion of the structure was unambiguously confirmed by X-ray crystallography. The optical properties were explored through UV-Vis absorption, fluorescence, and phosphorescence measurements, complemented by density functional theory (DFT) calculations. Remarkably, the pi-extended spiro-double carbo[7]helicene exhibited thermally activated delayed fluorescence (TADF) at room temperature and phosphorescence at low temperatures. Chiral HPLC successfully resolved the enantiomers into three fractions: (PP), (MM), and the meso forms (PM)/(MP), and chiroptical studies of the pure enantiomers revealed a moderately high g lum value of 1.58 x 10-3. Finally, the origin of the observed dissymmetry factors was rationalized by analyzing the transition electric dipole moments (TEDM) and transition magnetic dipole moments (TMDM) derived from time-dependent density functional theory (TD-DFT) calculations.

Chiroptical amplification of [7]-helicene nanographene by additional helical chirality - Dongre, Sangram D.; Venugopal, Geethu; Kumar, Viksit; Badrinarayan Jadhav, Ashok; Kumar, Jatish; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
Nanographenes have captivated scientific interest since the pioneering discovery of graphene. Recently, attention has shifted towards exploring chiral and nonplanar nanographenes, for their distinct optical, chiroptical, and electronic properties. Despite the growing acceptance of helicenes, the research on inducing helical chirality on pi-extended derivatives to boost chiroptical properties remains unattended. In our study, we introduce a new pi-extended [7]-helicene resulting from the condensation of diamines with 3,6-dibromophenanthrene-9,10-dione, complemented by two hexabenzocoronene arms in the periphery. Notably, the nanographene containing binaphtho-[1,4]diazocine, compared to the corresponding phenazine, exhibits a remarkable average 2.5, 5, and 10-fold enhancements in quantum yield, dissymmetry factor, and brightness, respectively, when measured in five different solvents. These improvements underscore the significance of the induced helical chirality by the antiaromatic binaphtho-[1,4]diazocine in influencing the chiroptical properties of the helical nanographene. Our research represents a significant stride toward unlocking the potential of pi-extended helicenes and lays the groundwork for further exploration in designing and synthesizing new chiral nanomaterials.
Keywords: circularly polarised luminescence; dissymmetry factor; helicene; nanographene; quantum yield